THE DEVELOPMENT OF TRADITIONAL AND ELECTRONIC FORMS OF THE BOOK IN THE CONTEXT OF INNOVATIVE TECHNOLOGIES - TIMUȚA, ALIONA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2023)
Modern technologies have a decisive impact on almost all spheres of human activity, thereby providing opportunities for the development of various forms of objects that are already familiar to us. This study is devoted to the research of new forms of printed and electronic books, the analysis of the specifics and features of the transformation of familiar forms in the context of the development of innovative technologies. An attempt was made to predict further development paths and prospects for long-term coexistence of traditional and electronic publications, areas of their confrontation and interaction.